On the formation and decay of a molecular ultracold plasma - Saquet, N; Morrison, J; Schulz-Weiling, M; Sadeghi, H; Yiu, J; Rennick, C; Grant, E (2011)
Double-resonant photoexcitation of nitric oxide in a molecular beam creates a dense ensemble of 50f(2) Rydberg states, which evolves to form a plasma of free electrons trapped in the potential well of an NO+ space charge. The plasma travels at the velocity of the molecular beam and, on passing through a grounded grid, yields an electron time-of-flight signal that gauges the plasma size and quantity of trapped electrons. This plasma expands at a rate that fits with an electron temperature as low as 5 K, colder than typically observed for atomic ultracold plasmas. The recombination of molecular NO + cations with electrons forms neutral molecules excited by more than twice the energy of the NO chemical bond, and the question arises whether neutral fragmentation plays a role in shaping the redistribution of energy and particle density that directs the short-time evolution from Rydberg gas to plasma. To explore this question, we adapt a coupled rate-equations model established for atomic ultracold plasmas to describe the energy-grained avalanche of electron-Rydberg and electron-ion collisions in our system. Adding channels of Rydberg predissociation and two-body, electron-cation dissociative recombination to the atomic formalism, we investigate the kinetics by which this relaxation distributes particle density and energy over Rydberg states, free electrons and neutral fragments. The results of this investigation point to conditions under which such processes can effect the steady-state temperature of plasma electrons. © 2011 IOP Publishing Ltd.